Morpho‐functional characterization of the submucosal glands at the nasopharyngeal end of the auditory tube in humans. Issue 5 (23rd December 2022) - Kumari, Chiman; Gupta, Richa; Sharma, Mayank; Jacob, Justin; Narayan, Ravi K.; Sahni, Daisy; Kumar, Ashutosh
Abstract: Background: The auditory tube (AT), an osteocartilaginous channel, connects the nasopharynx to the middle ear cavity. At the nasopharyngeal opening of the AT, there are dense collections of submucosal glands. In a recent article, Valstar et al. proposed these nasopharyngeal tubal glands conglomerate as salivary glands, which starkly contrasts with their previously known anatomy for being a component of the respiratory tract. This study examines the contesting views regarding the taxonomical categorization of the nasopharyngeal tubal glands. Materials and Methods: The AT glands in context were examined in human cadavers grossly, and microscopically using routine and special (Hematoxylin and Eosin [H&E] and Periodic acid–Schiff [PAS] respectively), as well as immunohistochemical (for alpha‐SMA and salivary amylase) staining methods and compared with the major and minor salivary glands and the submucosal glands in the trachea. Further, a biochemical analysis was performed to detect the presence of salivary amylase in the oral and nasopharyngeal secretions of the four living human subjects, representing major salivary glands and tubal glands, respectively. Results: The submucosal seromucous glands with a surface lining of respiratory epithelium were observed at the nasopharyngeal end of AT. The cells in the tubal glands showed cytoplasmic positivity for alpha‐SMA, which indicated the presence of the myoepithelial cells; however, this expression was significantly lower than in the seromucous submucosal glands within the trachea. Salivary alpha‐amylase was undetectable in the cadaveric tissue samples. Moreover, the amylase level in the nasopharyngeal swabs was negligible compared to the oral swabs. Conclusion: The anatomical location along the respiratory tract, the presence of respiratory epithelium in the overlying mucosa, their morpho‐functional resemblance to the seromucous glands in the trachea, and the absence of salivary amylase strongly indicate that the tubal glands are taxonomically different from the salivary glands. Given the available evidence, their existing recognition as a part of the respiratory tract and an integral component of the AT seems more appropriate. Abstract : In a recent article, Valstar et al. proposed the tubal glands conglomerate at the nasopharyngeal opening of the auditory tube (AT) in humans as salivary glands, which starkly contrasts with their previously known anatomy for being a component of the respiratory tract and an integral part of the AT. In this study, we examined the contesting views regarding the taxonomical categorization of these glands. Based on the findings, we recommend maintaining their existing recognition.